Spatial and temporal variability of phytoplankton photophysiology in the Atlantic Southern Ocean - Singh, Asmita; Thomalla, Sandy J.; Fietz, Susanne; Ryan-Keogh, Thomas J. (Frontiers in Marine Science, 2022)
Active chlorophyll-a fluorescence was measured during five summer research cruises (2008 – 2016), spanning the Atlantic sector of the Southern Ocean. This unique data set provides information for assessing zonal, inter-annual and intra-seasonal variability (early versus late summer) of photosynthetic efficiency (Fv/Fm). The zonal variability of Fv/Fm showed a typical latitudinal decline from a maximum in the Polar Frontal Zone (PFZ) (0.24±0.03) to a minimum in the Southern Antarctic Circumpolar Current Zone (SACCZ) (0.18±0.07). The inter-annual variability in Fv/Fm (between each cruise) was the highest in the SACCZ, while the Antarctic Zone (AZ) exhibited low inter-annual variability. Intra-seasonal variability between the zones was limited to a significantly higher mean Fv/Fm in the PFZ and AZ in early summer compared to late summer. Intra-seasonal variability between the cruises was, however, inconsistent as higher mean Fv/Fm in early summer were seen during some years as opposed to others. Ancillary physical and biogeochemical parameters were also assessed to investigate potential direct and indirect drivers of co-variability with Fv/Fm through a series of statistical t-tests, where significant differences in Fv/Fm were used as focus points to interrogate the plausibility of co-variance. Inter-zonal variability of surface seawater temperature (SST) and Silicate:Phosphate (Si:P) ratios were highlighted as co-varying with Fv/Fm in all zones, whilst community structure played an indirect role in some instances. Similarly, inter-annual variability in Fv/Fm co-varied with SST, Nitrate:Phosphate (N:P) and Si:P ratios in the PFZ, AZ and SACCZ, while community structure influenced inter-annual variability in the PFZ and SACCZ. Intra-seasonal variability in Fv/Fm was linked to all the ancillary parameters, except community structure in the AZ, whilst different ancillary parameters dominated differences during each of the cruises. These results were further scrutinized with a Principal Component Analysis for a subset of co-located data points, where N:P and Si:P ratios emerged as the principal indirect drivers of Fv/Fm variability. This study highlights the scope for using Fv/Fm to reflect the net response of phytoplankton photophysiology to environmental adjustments and accentuates the complex interplay of different physical and biogeochemical parameters that act simultaneously and oftentimes antagonistically, influencing inter-zonal, inter-annual and intra-seasonal variability of Fv/Fm.